The Economic Analysis of State Aid : Some Open Questions - Buelens, Christian; Garnier, Gaelle; Meiklejohn, Roderick; Johnson, Matthew; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
The last few years have seen both a significant shift in EU state aid policy towards a more sophisticated economic approach and a great enrichment of the economic literature on state aid. This paper examines the control of state aid in the EU in the light of the new literature. It begins with a discussion of the objectives of state aid control, taking account of the principle of subsidiarity. We discuss whether state aid control should concentrate on limiting the effects of aid on trade and competition (i.e. harm to rivals) or whether the purpose is broader and includes also considerations such as avoiding government failures and encouraging Member States to use state aid more sparingly and target it more efficiently. This leads to a brief analysis of how the appropriate welfare standard to be applied in state aid control would vary according to the weight given to different objectives. The paper then considers the objectives pursued by governments in granting aid with particular emphasis on the concept of market failure. The nature and magnitude of the market failure addressed by a state aid, together with the design of the aid, will strongly influence the extent of any anti-competitive effects. The last two parts (4 and 5) of the paper are devoted to specific problems of assessing anti-competitive effects using the types of information normally available to the aid-granting authorities and the European Commission. Part 4 discusses the problem of assessing the effects on competition of aid schemes and broad classes of aid, when the beneficiaries and even the affected markets are not known. Because Member States grant a vast number of individual aids every year, the Commission has to apply simple criteria to screen out those aids that are unlikely to have significant anti-competitive effects. We survey a range of indicators that can be used for this purpose and conclude that they all have drawbacks. Part 5 deals with the problems of assessing individual awards of aid which have failed the screening test, discussing how the main characteristics of firms (e.g. market share, vertical integration) and markets (such as product differentiation and market growth) may influence a state aid's impact on competition.
Economic Papers